Effect of Parenteral Antioxidant Supplementation During the Dry Period on Postpartum Glucose Tolerance in Dairy Cows. (12th March 2016) - Abuelo, A.; Alves‐Nores, V.; Hernandez, J.; Muiño, R.; Benedito, J.L.; Castillo, C.
Abstract : Background: Exacerbated postparturient insulin resistance (IR) has been associated with several pathologic conditions in dairy cattle. Oxidative stress (OS) plays a causative role in IR in humans, and an association, but not direct relationship, between OS and IR recently has been reported in transition dairy cattle. Hypothesis: Supplementation with antioxidants shortly before calving improves glucose tolerance after parturition in dairy cattle. Animals: Ten late‐pregnant Holstein cows entering their 2nd to 5th lactation. Methods: Randomized placebo‐controlled trial: 15 ± 2 days before expected calving, the treatment group received an injection of DL‐alpha‐tocopheryl acetate at a dosage of 6 mg/kg body weight (BW) and 0.06 mg/kg BW of sodium selenite, and the control group was injected with isotonic saline. During the first week after calving, both groups underwent glucose tolerance testing (0.25 g glucose/kg BW). Commercial assays were used to quantify the concentrations of glucose, insulin, nonesterified fatty acids (NEFA), beta‐hydroxybutyrate, and markers of redox status in blood. Data were analyzed using the Mann–Whitney U ‐test (α = 0.05). Results: Supplemented cows showed a lower risk for OS, as reflected by a lower OS index ( P = .036), different areas under the curve for the concentrations of glucose ( P < .01), insulin ( P = .043), and NEFA ( P = .041), more rapid elimination rates ( P = .080, <.01 and .047 respectively), and shorter half‐lives ( P = .040, <.01 and .032) of these metabolites. Conclusions and Clinical Importance: Supplementation with antioxidants before calving resulted in greater insulin sensitivity after calving, thereby suggesting the role of OS in the development of IR in cattle and the potential benefits of antioxidant supplementation in minimizing the consequences of negative energy balance.